Tracheal extubation and reintubation of the critically ill - challenges coming and going - Parotto, Matteo (Crit Care, 2015)
Tracheal reintubation is a common event in critical care. Elmer and colleagues provide the first comparison of complication rates of initial and subsequent reintubation(s) during the same hospitalization. Their work shows an increased risk of complications associated with reintubation, in particular hypoxemia and hypotension, reminding us to be cautious with patients having minimal reserve and potentially altered airway anatomy. See related research by Elmer et al., http://ccforum.com/content/19/1/12